Analisis Faktor Penyebab Ketidaktercapaian Target Output Produksi Cable Modem pada Line FATP - Sherly, Sherly (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
ABC Company is a company engaged in the manufacturing industry with one of its superior products in the form of cable modems. In carrying out production operations, the company has set a production output target of 95% each month to be able to pursue product delivery timeliness. However, under uctual conditions the company is only able to produce cable modem output of 74.65% of the total planned production target, this condition results in the company experiencing losses from complaints filed by consumers. This study aims to identify the factors causing the non-achievement of cable modem product output targets that occur in Line FATP. The research data was collected through a questionnaire instrument to 75 workers involved in the cable modem production process. The data was analyzed using quantitative descriptive analysis techniques using the factor analysis method. Based on the results of the study, there are two factors that affect the non-achievement of production output targets, namely the Facility Factor with an eigenvalue of 2.593% and the resource factor with an eigenvalue of 1.016%.